One-visit root canal treatment of the mandibular right second molar teeth: Perawatan saluran akar satu kali kunjungan pada gigi molar kedua kanan rahang bawah - Nurlaela Tahir; Christine Anastasia Rovani (Makassar Dental Journal PDGI Makassar, 2022)
One-visit root canal treatment (OV-RCT) aims to preserve damaged teeth by fulfilling the principles of the endodontic triad (cleaning and shaping, sterilizationand root canal obturation) which are completed in OV; the advantage is lower risk of bacterial contamination, shorter time without compromising the quality oftreatment results. This case report discusses OV-RCT of man-dibular right second molar. A 23-year-old woman with a diagnosis of asymptomatic irreversible pulpitis in the mandibular mo-lar, radiographically showed slight widening of the periodontal ligament. One-visit RCT was performed using Protaper Next ro-tary files on the mesiobuccal and mesiolingual roots up to X2 files (#25/06) and X3 files (#30/07) on the distal roots. The root canals were irrigated using 5.25%NaOCl and 17% EDTA. The root canal filling technique was carried out using a single cone technique using an epoxy resin sealer and gutta percha material. The treatment was successfully carried out. It was concluded that OV-RCT of the right lower second molar showed success both clinically and radiographically.